0832 Nocturnal Tachypnea with Non-Invasive Ventilation; A case report. (25th May 2022) - Elballat, Mohammad; Anderson, William; Patel, Kevin
Abstract: Introduction: We present a case of nocturnal tachypnea secondary to suspected auto-triggering in a patient on Bilevel device. Auto-triggering is a patient-ventilator asynchrony in which a ventilator breath is triggered in the absence of inspiratory muscle activity. This phenomenon was mostly described in postcardiac surgery and in brain dead patients on mechanical ventilation. Detecting this asynchrony is important as it can lead to patient discomfort, poor compliance and hypocarbia that can lead to apneic events. Report of Cases: An 82-year-old male with history of chronic atrial fibrillation, coronary artery disease (s/p bypass surgery) and Ischemic cardiomyopathy (EF 25-30%). He had moderate obstructive sleep apnea with central apnea. He was started on AutoPAP then was upgraded to BPAP (IPAP 16/EPAP 9 cmH2O). His wife reported episodes of nocturnal tachypnea and increased daytime somnolence. This was confirmed by the compliance reports from his BPAP device, and a portable sleep study obtained while using the BPAP (respiratory rate > 40 breaths/minute). Conclusion: Vignaux et al estimated the incidence of auto-triggering with NIV to be 13%. This phenomenon can be caused by a major circuit leak or secondary to cardiogenic oscillations. Effect of cardiogenic oscillation on the pulmonary air flow was described by West and Hugh-Jones in 1961. Our patient had dilated cardiomyopathy with hyperdynamic circulation which we believe was the major cause of his auto-triggering asynchrony. Changes in intracardiac volume and cardiac movements during systole resulted in intrapulmonary flow oscillations exceeding the set flow-trigger threshold leading to the tachypnea. In our patient, the events resolved after cardiac resynchronization procedure that improved the overall cardiac function and adjusting the trigger sensitivity. Support (If Any): [1]Kondili E, Prinianakis G, Georgopoulos D.; Patient ventilator interaction, Br J Anaesth. 2003; 91: 106-119 [2] Richard Arbour; Cardiogenic Oscillation and Ventilator Autotriggering in Brain-Dead Patients: A Case Series. Am J Crit Care 1 September 2009; 18 (5): 496–488. doi: https://doi.org/10.4037/ajcc2009690 [3] Imanaka, Hideaki MD; Nishimura, Masaji MD; Takeuchi, Muneyuki MD; Kimball, William R. MD, PhD; Yahagi, Naoki MD; Kumon, Keiji MD Auto-triggering caused by cardiogenic oscillation during flow-triggered mechanical ventilation, Critical Care Medicine: February 2000 - Volume 28 - Issue 2 - p 402-407 [4]Vignaux L, Vargas F, Roeseler J, Tassaux D, Thille AW, Kossowsky MP, et al. Patient-ventilator asynchrony during non-invasive ventilation for acute respiratory failure: a multicenter study. Intensive Care Med 2009;35(5):840–846